The Friction in Evidence Law: Criticism on Evidence of Negative Wettelijk Bewijstheorie in Tax Crimes - M Hary Djatmiko; Mira Sri Rahayu; Owoade Abdul Lateef (Unissula, 2025)
Enforcement of criminal tax law is still a complex problem with the application of the theory of positive legal evidence replacing the theory of negative legal evidence, prioritizing formal evidence over court decisions. This study aims to analyze criticism of the application of evidentiary law in the due process of law of tax crimes and describe the shift in the application of the negative legal evidence theory. This study uses a normative juridical method. The application of negative legal evidence in criminal decisions has been criticized for its strict assessment of evidence, the inability of the Tax Court to handle criminal tax cases even though the taxation contains criminal elements, and the judge's dependence on legally valid evidence based on personal beliefs. The assessment of evidence primarily functions as formal evidence or authentic evidence, with witness statements serving as supporting evidence to confirm fraudulent transactions. The novelty of this analysis lies in its critical examination of the negative legal theory, arguing that in cases of tax crimes, formal documentary evidence has greater evidentiary value, thus leading to the dominance of the positive legal theory in legal reasoning.